2022
DOI: 10.1021/acsaelm.2c00379
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Engineering of TMDs by Modulation of Top Chalcogen Atoms: For Electrical Contact and Chemical Doping

Abstract: To achieve high-performance electronic and optoelectronic devices based on two-dimensional transition-metal dichalcogenides (2D TMDs), it is necessary to solve the contact resistance issue caused by the energy barrier at the interface between metal electrodes and the 2D semiconductor. By use of a controlled Ar + ion beam with a threshold ion energy of 25 eV, the top sulfur layer only was successfully removed from the monolayer molybdenum disulfide (MoS 2 ), and the semiconductor to metallic transition (MT) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…This result has demonstrated the importance of choosing a suitable metal catalyst for the removal of 2D materials with precise uniformity and purity in the LRS and MAS methods. To date, the integrated cyclic plasma thinning 74,76,77,[105][106][107][108] and LRS 89 methods are considered as two of the best methods for fabricating 2D material thinning due to their advantages and unique capabilities in comparison to the other thinning methods such as plasma-assisted thinning, ALT, laser-assisted thinning, and MAS. Some of the parameters in these two methods can overcome the limitations that are involved in other methods.…”
Section: The Influence Of Technologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…This result has demonstrated the importance of choosing a suitable metal catalyst for the removal of 2D materials with precise uniformity and purity in the LRS and MAS methods. To date, the integrated cyclic plasma thinning 74,76,77,[105][106][107][108] and LRS 89 methods are considered as two of the best methods for fabricating 2D material thinning due to their advantages and unique capabilities in comparison to the other thinning methods such as plasma-assisted thinning, ALT, laser-assisted thinning, and MAS. Some of the parameters in these two methods can overcome the limitations that are involved in other methods.…”
Section: The Influence Of Technologiesmentioning
confidence: 99%
“…12 and Table 1). 60,66,75,76,80,89,107,108,111,112,[120][121][122][123][124][125][126][127][128][129] These 2D materials possess a wealth of electronic and optoelectronic properties, encompassing light emission, optical modulation, saturable adsorption, and electrically modulated field effect characteristics. [130][131][132][133][134][135][136][137][138] Harnessing these unique properties, significant endeavors have been channeled towards the exploration of 2D materials-based on electronic and optoelectronic applications, capitalizing on the advantages that are offered by top-down thinning strategies.…”
Section: Semiconducting Devices Associated With Atomical Layer-by-lay...mentioning
confidence: 99%
See 1 more Smart Citation
“…The Svacancies create shallow trap states, while TM vacancies are associated with deep-trap states. Kim et al 41 experimentally demonstrated that S-vacancies induce more impurities and disorders in WS 2 than W-vacancies, resulting in a 10-fold higher doping concentration and a 4-fold higher Coulomb scattering coefficient. This is attributed to the formation of shallow doping levels within the bandgap due to S-vacancies, making them chemically active.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As a relatively new class of layered materials, 2D transition metal dichalcogenides (TMDs) have attracted significant attention in the last few decades due to their semiconducting characteristics, excellent chemical stability, and tunable mechanical and physical properties. They find applications in a wide variety of fields: A relatively high electrical conductivity and a relatively low thermal conductivity make TMDs promising materials for next-generation high-performance thermoelectric devices. Monolayer WSe 2 , due to its heavy atom mass and low Debye frequency, has been found to have ultralow thermal conductivity, even lower than that in MoS 2 . , The observations and understanding derived from the studies of the corresponding bulk nanostructured materials have stimulated further research on thermoelectric energy conversion …”
Section: Introductionmentioning
confidence: 99%